Protein kinase C plays no role in KCl-induced vascular contraction in Ca(2+)-free medium - Kwan Chiu-Yin; Kravtsov Gennadi M (Acta Pharmacologica Sinica, 2016)
AIM: To examine the role of protein kinase C (PKC) on the sustained contractile responses of rat aorta to high KCl in isotonic Ca(2+)- and Mg(2+)-free solutions. METHODS: The effects of phorbol 12-myristate 13-acetate (PMA, a PKC activator) and Calphostin C (a selective PKC inhibitor) were observed on the sustained contraction of rat aorta induced by K+ 136 mmol.L-1. EGTA (100 mumol.L-1) was added to prepare the Ca(2+)-free medium and EDTA (100 mumol.L-1) was added to reduce or remove the Mg2+. RESULTS: Aortic contraction to KCl was prominent in low Mg2+ medium and was enhanced by EDTA (K-EDTA contraction). Such contraction was concentration-dependently inhibited by Mg2+, but was not affected by Calphostin C 1 mumol.L-1. Pretreatment of the aortic preparations with PMA (0.8 mumol.L-1) potentiated the contraction to KCl in Ca(2+)-free, low Mg2+ medium and higher concentration of Mg2+ was required to cause relaxation. Such a reduced sensitivity to Mg2+ in the presence of PMA was partially reversed by Calphostin C and was accompanied by an increased sensitivity to Ca2+, which concentration-dependently caused contraction following Mg(2+)-induced relaxation. However, in the presence of EDTA 100 mumol.L-1 (eg, Mg(2+)-free medium), the maximal contraction to KCl in Ca(2+)-free medium was not affected by PMA or Calphostin C. CONCLUSION: KCl-induced contraction in Ca(2+)-free and Mg(2+)-free + EDTA 100 mmol.L-1 medium was not affected by PMA or Calphostoin C, indicating that PKC plays no role in such contractile responses.